Environmental and economic assessment of the Inbicon lignocellulosic ethanol technology. (1st June 2016) - Zech, Konstantin M.; Meisel, Kathleen; Brosowski, André; Toft, Lars Villadsgaard; Müller-Langer, Franziska
Highlights: The Inbicon lignocellulosic ethanol technology is analysed considering 14 scenarios. Feedstock, pentose-use, process energy, enzyme production and location are varied. Simulation results are based on real data gathered in the Inbicon demonstration plant. Competitive bioethanol provision costs between 17.6 and 39.2 EUR GJ −1 . GHG emission savings between 52% and 87% compared to the fossil reference. Abstract: Inbicon's lignocellulose-to-bioethanol technology is assessed in terms of its environmental and economic performance within this article. This is done under various scenarios to identify the influence of locations, raw materials and plant setups on the results. In all scenarios the specific GHG emissions of the bioethanol production are 50% below those of the fossil reference fuel, some scenarios even reach a GHG mitigation of over 60%. In many scenarios specific production costs are reached that are in the range or below those of conventional bioethanol today. But low emissions and low costs remain contradictory targets to a great extent. However, using C5 sugars in co-fermentation to produce bioethanol and the also generated biogas as an internal heat source seems to be a good compromise and leads to both relatively low costs of 27.2 EUR GJ −1 and low emissions of 28.3 kg CO2 -eq. GJ −1 .